Comparison Of AHP And Topsis Methods In Determining Scholarships For Elementary School Students - Efansius Tarigan (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2022)
The regional coordinator of the Siantar sub-district is the education office in the Siantar sub-district. The office is used to store elementary school student data in the Siantar sub-district before it is submitted to the education office in Simalungun district. In collecting data on students in each school, employees sometimes find it difficult to filter out which students have the highest grades in each elementary school and determine who deserves assistance from the Simalungun Regency Government for those who excel. Therefore, the comparison of the AHP and TOPSIS methods in determining the scholarships for elementary school students at the Siantar District Regional Coordinator is to carry out a ranking of alternatives in the form of student data. The AHP and TOPSIS methods are compared because this method determines the weight value for each attribute, which is followed by ranking a number of available options and then re-selected to find the best choice.